MCDA-AHP-GIS-Based Site Suitability Assessment for a Multi-Utility Tunnel in Panakkukang Sub-district, Makassar City , Indonesia - Muthalib, Ade Nirwani Abdurahman; Rumata, Nini Apriani; Burhanuddin, Fathurrahman; Faisal, Muhammad; Firdaus; Rahmania; Bakti , Rizki Yusliana (UIR PRESS, 2026)
This study develops a transparent MCDA–AHP–GIS framework to screen Multi-Utility Tunnel (MUT) corridor suitability in Panakkukang Sub-district, Makassar City, using 2024 baseline datasets and five criteria: utility/network density (C1), road functional class and corridor capacity (C2), flood susceptibility (C3), activity intensity (C4; proxied by kelurahan-level population density), and spatial planning compatibility with RTRW/RDTR (C5). All layers were standardized and reclassified (1–3 or 1–5) and integrated using Weighted Linear Combination (WLC) with AHP-derived weights (CR = 0.028), where C1 (0.26) and C5 (0.24) were highest, followed by C2 (0.19), C4 (0.16), and C3 (0.15). The 2,918.3-ha study area was classified into Very Unsuitable (88.2 ha; 3.0%), Unsuitable (405.8 ha; 13.9%), Moderately Suitable (764.9 ha; 26.2%), Suitable (935.8 ha; 32.1%), and Highly Suitable (723.6 ha; 24.8%). A corridor-focused overlay shows that 436.9 ha fall within the Suitable–Highly Suitable mask, of which 127.3 ha (29.1%) intersect high flood-hazard zones, indicating that some priority segments require attention during detailed planning. Uncertainty mainly arises from buffer distances and reclassification thresholds and from non-differentiating attributes in some utility layers; however, a ±10% weight sensitivity test yields only minor shifts in class areas and preserves the main priority-corridor pattern.